Afecting Factors Consumer Satisfaction of Traditional Cakes Kak Nur's UMKM in Langung Village, Meurebo District, West Aceh Regency: FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN KUE TRADISIONAL UMKM KAK NUR DI DESA LANGUNG KECAMATAN MEUREBO KEBUPATEN ACEH BARAT - Liston Siringo Ringo; Dedy Darmansyah; Khairun Nisa; Irma Wahyuni (ROCE : Jurnal Pertanian Terapan, 2024)
Consumer satisfaction is the main key to the success of culinary businesses, including Kak Nur's UMKM. Factors such as product quality, price, service, and product innovation play a major role in determining the level of consumer satisfaction. This research aims to identify and analyze the factors that influence consumer satisfaction with traditional cakes produced by Kak Nur UMKM in Langung Village, Meurebo District, West Aceh Regency. We conducted this research from January to June 2024. The data analysis methods used were descriptive analysis, regression analysis, coefficient of determination test, T test, and F test. The results of the study showed that product quality, price, and service variables had a positive and significant effect on consumer satisfaction of Kak Nur's traditional MSME cakes. Based on the adjusted R square value of 0.715, which means that the independent variables are product quality, price, and service, they are able to explain 71.50 percent of the dependent variable, namely consumer satisfaction, and the remaining 28.50 percent is explained by other variables not studied.